The central-bank balance sheet as an instrument of monetary policy - Vasco Cúrdia; Michael Woodford (Federal Reserve Bank of New York, 2010)
While many analyses of monetary policy consider only a target for a short-term nominal interest rate, other dimensions of policy have recently been of greater importance: changes in the supply of bank reserves, changes in the assets acquired by central banks, and changes in the interest rate paid on reserves. We first extend a standard New Keynesian model to allow a role for the central bank's balance sheet in equilibrium determination and then consider the connections between these alternative policy dimensions and traditional interest rate policy. We distinguish between 'quantitative easing' in the strict sense and targeted asset purchases by a central bank, arguing that, according to our model, while the former is likely to be ineffective at all times, the latter can be effective when financial markets are sufficiently disrupted. Neither is a perfect substitute for conventional interest rate policy, but purchases of illiquid assets are particularly likely to improve welfare when the zero lower bound on the policy rate is reached. We also consider optimal policy with regard to the payment of interest on reserves; in our model, this requires that the interest rate on reserves be kept near the target for the policy rate at all times.
Keywords: E50; E52; E58; 330; Credit policy; quantitative easing; zero lower bound